INVESTIGATION OF WATERMELON AND MELON DOMESTIC SELECTION IN THE SOUTHERN ZONE OF THE AMUR REGION - E. V. Sunyaikina; V. F. Kirsanova; A. S. Sokolov (Овощи России)
Melon crops have long been non-traditional crops in the Amur region, being grown in small quantities in household plots, while the climatic conditions of Southern Priamurie are favorable for their large-scale cultivation. The results of the study of 10 samples of watermelon and 4 samples of melons of domestic selection in the conditions of the southern zone of Amurskaya Oblast are presented. According to the evaluation of the collection, 7 samples of watermelon are selected: Start, Graal F1, Fronder, Vektor, Skorik, Rapid, Foton, and 2 samples of melon: Alisa F1 and Lolita. They are characterized by sufficiently early ripeness, high and stable yield of marketable fruits of good taste. These varieties and hybrids are promising for cultivation in the south of Amurskaya Oblast. The characteristics of these varieties are summarized and recommendations for their cultivation are offered.